Kabus - kabus memori (cloud of memories) / Tazul Tajuddin - Tajuddin, Tazul (Faculty of Music, 2018)
Kabus-kabus Memori means 'Clouds of Memories'. It is a collection of short and easy pieces, in this project for solo piano initiated by Dr Tham Kent Horng. Dr Tham is researching and recording some of my early piano works. This collection is commissioned by Dr Tham. It consists of 6 solo piano pieces which are: 1. Sebuah Pantun, 2. Meditasi Lagu Dalam Mimpi, 3. A Tango Waltz, 4. Pantun - Rawak, 5. Meditasi Dalam Mimpi V, 6. Kabus Pantun. Clouds of Memories are collection of pieces from the past, some are revisited work and some are used previous materials as based for new one. Time here is past memories, clouds that shrouded the memories, some are clear and some are misty. This collection is a shred of this memory. As human, time is as our one's own moment and past memories preserved but no memories of the future exist except imagined or predicted one. I would like to extend my expression of gratitude to Dr Tham for the commissioning, performing and recording the works and many thanks to his team, Dr Yen Lin Goh as the co-researcher and pianist. I hope the project would continue to benefit the younger generations of musicians and composers and to preserved and documented some musical memories too. Kabus-kabus Memori is dedicated to Tham Kent Horng.